Kidney supportive care in advanced chronic kidney disease: a qualitative meta-synthesis of healthcare professionals perspectives and attitudes - Xue Li; Wei Ji; Dou Wang; Ying Xu; XinYu Zhao; SiYuan Liang (BMC Nephrology)
Abstract Aims This study systematically reviews and synthesizes healthcare professionals’ perspectives on Kidney Supportive Care (KSC) to establish an evidence base for enhancing its clinical dissemination and implementation. Background KSC enhances end-of-life care quality for renal patients through a patient-centered framework integrating shared decision-making and advance care planning. This anticipatory transition management in advanced kidney disease seeks to alleviate patient/family distress while optimizing end-of-life care experiences. While KSC adoption in kidney disease care remains emergent globally, strategic investigation is critical to strengthen clinical integration. Design A systematic review and integration of qualitative studies conducted in accordance with ENTREQ guidelines. Review Methods We systematically searched ten databases, including PubMed, Web of Science, Embase, Cochrane Library, CINAHL, Science Direct, CNKI, Wanfang Data, VIP, and CBM, spanning from inception to February 29, 2024. This study systematically synthesizes qualitative evidence on clinician perspectives regarding KSC in end-stage renal disease. Methodological rigor was evaluated using Joanna Briggs Institute’s (JBI) 2020 Qualitative Research Appraisal Criteria. Primary study data underwent convergent synthesis following established methodology. Results Eight studies yielded 10 subordinate and 5 core themes: Professional Role Challenges, Pre-implementation cognitive-ethical conflicts, Post-decisional operational barriers, Systemic and Institutional Issues, Patient-Centered and Ethical Care. Conclusions KSC is recognized as a novel therapeutic paradigm in nephrology, demonstrating significant translational promise. However, clinical implementation confronts multifaceted barriers. Future research should prioritize implementation by incorporating multidisciplinary perspectives (patients, clinicians, families). Ongoing policy framework optimization must underpin sustainable KSC implementation and progression in clinical practice. Relevance to clinical practice These findings elucidate clinician perspectives regarding KSC clinical translation. Nurses’ strategic formulation of integrated intervention frameworks requires prioritization as pivotal KSC stakeholders. This initiative is imperative for enhancing care delivery in ESRD clinical practice. Clinical trial number Not applicable.